Widespread desert affiliation of trebouxiophycean algae (Trebouxiophyceae, Chlorophyta) including discovery of three new desert genera. Issue 4 (27th August 2014) - Fučíková, Karolina; Lewis, Paul O.; Lewis, Louise A.
Summary Unlike most other green algae, trebouxiophyceans are predominantly aerophytic and contain many symbiotic representatives. In recent years, a number of new terrestrial trebouxiophycean taxa were described from soils, tree bark, and lichens. The present phylogenetic study reveals three new lineages of free‐living trebouxiophyceans found in North American desert soil crusts and proposes new generic names to accommodate them: Desertella, Eremochloris, and Xerochlorella. This survey of desert isolates also led to discovery of representatives of seven existing genera of trebouxiophyceans. Two of these genera have never been reported to contain desert representatives and one was known previously only from aquatic habitats. Furthermore, we expand the known geographic range of the recently described genus Chloropyrula, heretofore only known from the Ural Mountains. We demonstrate that the diversity of trebouxiophyceans is still underestimated and poorly understood, and that most major trebouxiophycean lineages contain desert‐dwelling taxa.